Effects of nitrogen on the response of loblolly pine to drought II. Biomass allocation and C : N balance - Green, Thomas H (The New phytologist, 1994)
Effects of drought on carbon and nitrogen dynamics and biomass allocation patterns of loblolly pine (Pinus taeda L.) seedlings grown under 4 different nitrogen levels were determined Nitrogen stress caused an increase in root-shoot ratio. increased Foliar and mot Starch concentration, decreased soluble sugar concentration, and decreased free amino acid concentration in well-watered seedlings. Drought cent-rally caused an increase in foliar hexoses and decreases in foliar find root starch and root hexoses. while not affecting foliar free amino acids. However, nitrogen stress arid drought interacted in affecting carbohydrate pools and seedling morphology. Foliar starch reserves in high-N seedling were rapidly metabolized under drought, white N-deficient seedling maintained similar starch concentrations throughout the drought stress cycle. After one drought cycle, the N-induced difference in root:shoot ratio was no longer significant. These results suggest that N-stressed seedlings partition a higher percentage of fixed carbon to storage, and that (his storage pool is less available For immediate Use than in seedlings grown under adequate N